Bile detection of squamous cell carcinoma antigen (SCCA) in extrahepatic cholangiocarcinoma. Issue 4 (April 2023) - Gringeri, E.; Biasiolo, A.; Di Giunta, M.; Mescoli, C.; Guzzardo, V.; Sartori, A.; Cirillo, G.; Nieddu, E.; D'Amico, F.E.; Pontisso, P.; Cillo, U.
Abstract: Background: Cholangiocarcinoma (CCA) is a rare biliary tract tumor with poor prognosis that often is challenging to diagnose and the majority of patients present with advanced stage. Squamous cell carcinoma antigen 1 (SCCA1) overexpression has been found in different tumors associated with poor prognosis and chemoresistance. Aims: To assess the presence and possible prognostic role of SCCA1/2 isoforms in bile and serum of patients with CCA. Methods: Forty seven surgical patients (36 with CCA and 11 with benign diseases) were prospectively included in the study. Serum and bile specimens were collected at the time of surgery and free and IgM-complexed SCCA was quantified by ELISA (Xeptagen, srl). Results: Free or IgM linked SCCA was rarely found in serum, while SCCA was detectable in bile samples of patients with CCA, especially in those with extrahepatic form (43% vs 17%, p  = 0.008), but not in controls. Despite similar tumor stage, these positive patients presented a trend toward a higher percentage of portal invasion (27% vs 15%) and of tumor recurrence than negative cases (62% vs 40%), although the difference was not statistically significant. Conclusion: These preliminary results indicate that bile testing for SCCA is a specific marker of extrahepatic CCA, with potential prognostic value.